Living Islam Through Disability-Inclusive Zakāh: Self-Transformation, Dignity, and Social Participation Among LAZISMU Beneficiaries - Haliza Deli Gayo; Fathin Robbani Sukmana; Miranti Indri Hastuti; Aytan Azizli (JURNAL INDO-ISLAMIKA, 2026)
This study examines how LAZISMU’s inclusive productive zakat intervention contributes to the self-transformation of persons with disabilities in Indonesia. While previous studies have largely focused on the economic outcomes of zakat distribution, this research explores how zakat operates as a catalyst for multidimensional self-transformation. Using a qualitative phenomenological approach, specifically Interpretative Phenomenological Analysis (IPA), this study draws on in-depth interviews with seven beneficiaries of LAZISMU’s inclusive economic program: five with visual impairments who received business capital assistance, and two with physical disabilities who received prosthetic support. The findings reveal that productive zakat functions not only as economic assistance but also as a catalyst for self-efficacy, social recognition of dignity, spiritual meaning-making, and social participation among persons with disabilities. However, this transformation occurs within persistent structural constraints, including limited market access, social stigma, inadequate post-disbursement mentoring, and infrastructural barriers. This study contributes to the literature on Islamic philanthropy by demonstrating that productive zakat should be evaluated not only by income indicators, but also by its capacity to foster agency, self-confidence, social participation, and spiritual resilience among marginalized mustahik. The study also highlights the need to integrate structural transformation including disability-sensitive mentoring, accessible infrastructure, and stable market access into empowerment programs for persons with disabilities.